Intercomparison of direct sampling methods of volcanic gases and implications for the determination of chlorine isotopic compositions in fumaroles - E. Le Glas; M. Bonifacie; F. Tassi; G. Bardoux; R. Moretti; V. Robert; E. Chilin-Eusebe; H. Balcone-Boissard; P. Agrinier (Journal of Volcanology and Geothermal Research, 2026)

The global role of bioassessment in policy delivery and decision-making for inland waters - Martyn G. Kelly; Gary Free; John P. Simaika; Stuart Warner; Andreas Bruder; Alejandra Correa-Bedoya; Fabio de Oliveira Roque; Tor Erik Eriksen; Jennifer Lento; Craig R. Macadam; Kristian Meissner; Marcelo S. Moretti; et al. (Journal of Environmental Management, 2025)

Factors influencing nitrogen derived from soil organic matter mineralisation: Results from a long-term experiment - Octavian P. Chiriac; Marco Pittarello; Barbara Moretti; Laura Zavattaro (Agriculture, Ecosystems & Environment, 2025)

Factors correlating with circulating T-zone-like cells of undetermined significance (TZUS) in dogs resident in Italy - V. Martini; P. Moretti; F. Sini; A. Ubiali; A. Poggi; F. Riondato (The Veterinary Journal, 2024)

Towards harmonized standards for freshwater biodiversity monitoring and biological assessment using benthic macroinvertebrates - John P. Simaika; James Stribling; Jennifer Lento; Andreas Bruder; Sandra Poikane; Marcelo S. Moretti; Nick Rivers-Moore; Kristian Meissner; Craig R. Macadam (Science of The Total Environment, 2024)

Allele and genotype frequencies for primary hereditary cataract, multifocal retinopathy 1, and degenerative myelopathy in Pyrenean Mountain dog from Italy - R. Moretti; G. Massimello; S. Chessa; S. Sartore; A. Tranchero; M. Profiti; P. Sacchi (Topics in Companion Animal Medicine, 2024)

How do macroconsumers interact with insect shredders in streams? A laboratory test using shrimp and caddisfly larvae that build cases with different organic materials - Pâmela Barbosa; Walace P. Kiffer; Larissa C. Costa; Flávio Mendes; Marcelo S. Moretti (Limnologica, 2023)

Hepatocellular carcinoma induced by hepatocyte Pten deletion reduces BAT UCP-1 and thermogenic capacity in mice, despite increasing serum FGF-21 and iWAT browning - Álbert S. Peixoto; Mayara F. Moreno; Érique Castro; Luiz A. Perandini; Thiago Belchior; Tiago E. Oliveira; Thayna S. Vieira; Gustavo R. Gilio; Caroline A. Tomazelli; Bianca F. Leonardi; Milene Ortiz-Silva; Luciano P. Silva Junior; et al. (Journal of Physiology and Biochemistry, 2023)

Feline injection-site sarcomas (FISSs): could the assessment of tumour-infiltrating lymphocytes (TILs) help in prog-nostic evaluations? - I. Porcellato; E. Treggiari; V. Gismondi; I. Di Matteo; C. De Feo; G. Moretti; P. Roccabianca; E. Lepri; M. Sforna; C. Brachelente (Journal of Comparative Pathology, 2023)

Sex-dependent modulation of caerulein-induced acute pancreatitis in C57BL/6J mice: histopathological and immunohistochemical characterization - L. Bertola; G. Pepe; A. Dolce; A. Cappelleri; S. Canesi; P. Moretti; A. Giordano; E. Scanziani; E. Vegeto; C. Recordati (Journal of Comparative Pathology, 2023)

Early nitrogen supply as an alternative management for a cover crop-maize sequence under a no-till system - Letusa Momesso; Carlos A. C. Crusciol; Rogério P. Soratto; Carlos A. C. Nascimento; Ciro A. Rosolem; Luiz G. Moretti; Eiko E. Kuramae; Heitor Cantarella (Nutrient Cycling in Agroecosystems, 2021)
Optimizing agronomic efficiency (AE) of nitrogen (N) fertilizer use by crops and enhancing crop yields are challenges for tropical no-tillage systems since maintaining crop residues on the soil surface alters the nutrient supply to the system. Cover crops receiving N fertilizer can provide superior biomass, N cycling to the soil and plant residue mineralization. The aims of this study were to (i) investigate N application on forage cover crops or cover crop residues as a substitute for N sidedressing (conventional method) for maize and (ii) investigate the supply of mineral N in the soil and the rates of biomass decomposition and N release. The treatments comprised two species, i.e., palisade grass [ Urochloa brizantha (Hochst. Ex A. Rich.) R.D. Webster] and ruzigrass [ Urochloa ruziziensis (R. Germ. and C.M. Evrard) Crins], and four N applications: (i) control (no N application), (ii) on live cover crops 35 days before maize seeding (35 DBS), (iii) on cover crop residues 1 DBS, and (iv) conventional method (N sidedressing of maize). The maximum rates of biomass decomposition and N release were in palisade grass. The biomass of palisade grass and ruzigrass were 81 and 47% higher in N application at 35 DBS compared with control in ruzigrass (7 Mg ha −1 ), and N release followed the pattern observed of biomass in palisade and ruzigrass receiving N 35 DBS (249 and 189 kg N ha −1 ). Mineral N in the soil increased with N application regardless of cover crop species. Maize grain yields and AE were not affected when N was applied on palisade grass 35 DBS or 1 DBS (average 13 Mg ha −1 and 54 kg N kg −1 maize grain yield) compared to conventional method. However, N applied on ruzigrass 35 DBS decreased maize grain yields. Overall, N fertilizer can be applied on palisade grass 35 DBS or its residues 1 DBS as a substitute for conventional sidedressing application for maize.

Use of radiofrequency electromagnetic radiation to remove biofilms from canvasses - P. Cennamo; N. Pasquino; C. Ciniglia; A. Moretti; P. Caputo (Aerobiologia, 2020)

Effects of Maternal Dietary Cottonseed on the Profile of Minerals in the Testes of the Lamb - Helder Louvandini; Egon H. Ieda; Carolina R. Jimenez; Patricia Spoto Corrêa; Debora B. Moretti; Paulo M. T. Lima; Concepta M. McManus; Hudson W. P. Carvalho; Elisabete A. De N. Fernandes (Biological Trace Element Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The longer the conditioning, the better the quality? The effects of leaf conditioning time on aquatic hyphomycetes and performance of shredders in a tropical stream - Cinthia G. Casotti; Walace P. Kiffer; Larissa C. Costa; Pâmela Barbosa; Marcelo S. Moretti (Aquatic Ecology, 2019)

Multisource data integration to investigate one century of evolution for the Agnone landslide (Molise, southern Italy) - M. Del Soldato; A. Riquelme; S. Bianchini; R. Tomàs; D. Di Martire; P. De Vita; S. Moretti; D. Calcaterra (Landslides, 2018)

Structural and functional composition of invertebrate communities associated with leaf patches in forest streams: a comparison between mesohabitats and catchments - Flávio Mendes; Walace P. Kiffer; Marcelo S. Moretti (Hydrobiologia, 2017)

Diversity of phototrophic components in biofilms from Piperno historical stoneworks - P. Cennamo; P. Caputo; C. Marzano; A. Z. Miller; C. Saiz-Jimenez; A. Moretti (Plant Biosystems, 2016)

Monitoring population‐level responses of marine mammals to human activities - Erica Fleishman; Daniel P. Costa; John Harwood; Scott Kraus; David Moretti; Leslie F. New; Robert S. Schick; Lisa K. Schwarz; Samantha E. Simmons; Len Thomas; Randall S. Wells (Marine Mammal Science, 2016)
We provide guidance for monitoring whether human activities affect the physiology or behavior of marine mammals and, if so, whether those effects may lead to changes in survival and reproduction at the population level. We suggest that four elements be included in designing and implementing such a monitoring program. The first is development of a theory of change: a set of mechanistic hypotheses that outline why a given activity might be expected to have one or more measurable effects on individuals and populations, and ideally the magnitude, timing, and duration of the effects. The second element, definition of biologically meaningful effect sizes, ultimately facilitates the development of a monitoring program that can detect those magnitudes of effect with the desired levels of precision. The third element, selection of response variables for monitoring, allows inference to whether observed changes in the status of individuals or populations are attributable to a given activity. Visual observations, passive acoustic and tagging instruments, and direct physical measurements all can provide data that facilitate quantitative hypothesis testing. The fourth element is specification of the temporal sequence of monitoring. These elements also can be used to inform monitoring of the responses of other taxonomic groups to human activities.

Impacts of urban sprawl on species richness of plants, butterflies, gastropods and birds: not only built-up area matters - Elena D. Concepción; Martin K. Obrist; Marco Moretti; Florian Altermatt; Bruno Baur; Michael P. Nobis (Urban Ecosystems, 2016)

Histochemical distribution of intestinal enzymes of juvenile pacu (Piaractus mesopotamicus) fed lyophilized bovine colostrum - Débora B. Moretti; Wiolene M. Nordi; Thaline M. P. Cruz; José Eurico P. Cyrino; Raul Machado-Neto (Fish Physiology and Biochemistry, 2014)

Geochemical and isotopic insights into the assembly, evolution and disruption of a magmatic plumbing system before and after a cataclysmic caldera-collapse eruption at Ischia volcano (Italy) - R. J. Brown; L. Civetta; I. Arienzo; M. D’Antonio; R. Moretti; G. Orsi; E. L. Tomlinson; P. G. Albert; M. A. Menzies (Contributions to Mineralogy and Petrology, 2014)

Selection of Multiple Umbrella Species for Functional and Taxonomic Diversity to Represent Urban Biodiversity - T. SATTLER; G. B. PEZZATTI; M. P. NOBIS; M. K. OBRIST; T. ROTH; M. MORETTI (Conservation Biology, 2014)
Surrogates, such as umbrella species, are commonly used to reduce the complexity of quantifying biodiversity for conservation purposes. The presence of umbrella species is often indicative of high taxonomic diversity; however, functional diversity is now recognized as an important metric for biodiversity and thus should be considered when choosing umbrella species. We identified umbrella species associated with high taxonomic and functional biodiversity in urban areas in Switzerland. We analyzed 39,752 individuals of 574 animal species from 96 study plots and 1397 presences of 262 plant species from 58 plots. Thirty‐one biodiversity measures of 7 taxonomic groups (plants, spiders, bees, ground beetles, lady bugs, weevils and birds) were included in within‐ and across‐taxa analyses. Sixteen measures were taxonomical (species richness and species diversity), whereas 15 were functional (species traits including mobility, resource use, and reproduction). We used indicator value analysis to identify umbrella species associated with single or multiple biodiversity measures. Many umbrella species were indicators of high biodiversity within their own taxonomic group (from 33.3% in weevils to 93.8% in birds), to a lesser extent they were indicators across taxa. Principal component analysis revealed that umbrella species for multiple measures of biodiversity represented different aspects of biodiversity, especially with respect to measures of taxonomic and functional diversity. Thus, even umbrella species for multiple measures of biodiversity were complementary in the biodiversity aspects they represented. Thus, the choice of umbrella species based solely on taxonomic diversity is questionable and may not represent biodiversity comprehensively. Our results suggest that, depending on conservation priorities, managers should choose multiple and complementary umbrella species to assess the state of biodiversity. Selección de Múltiples Especies Paraguas para la Diversidad Funcional y Taxonómica para Representar la Biodiversidad Urbana

Developing logistic models to relate the accumulation of DON associated with Fusarium head blight to climatic conditions in Europe - Xiangming Xu; Laurence V. Madden; Simon G. Edwards; Fiona M. Doohan; Antonio Moretti; L. Hornok; P. Nicholson; A. Ritieni (European Journal of Plant Pathology, 2013)

Estimating minke whale ( Balaenoptera acutorostrata ) boing sound density using passive acoustic sensors - Stephen W. Martin; Tiago A. Marques; Len Thomas; Ronald P. Morrissey; Susan Jarvis; Nancy DiMarzio; David Moretti; David K. Mellinger (Marine Mammal Science, 2013)
A bstract Density estimation for marine mammal species is performed primarily using visual distance sampling or capture‐recapture. Minke whales in Hawaiian waters are very difficult to sight; however, they produce a distinctive “boing” call, making them ideal candidates for passive acoustic density estimation. We used an array of 14 bottom‐mounted hydrophones, distributed over a 60 × 30 km area off Kauai, Hawaii, to estimate density during 12 d of recordings in early 2006. We converted the number of acoustic cues ( i.e. , boings) detected using signal processing software into a cue density by accounting for the false positive rate and probability of detection. The former was estimated by manual validation, the latter by applying spatially explicit capture‐recapture (SECR) methods to a subset of data where we had determined which hydrophones detected each call. Estimated boing density was 130 boings per hour per 10,000 km 2 (95% CI 104–163). Little is known about the population's acoustic behavior, so conversion from boing to animal density is difficult. As a demonstration of the method, we used a tentative boing rate of 6.04 boings per hour, from a single animal tracked in 2009, to give an estimate of 21.5 boing‐calling minke whales per 10,000 km 2 .

A Dutch field survey on fungal infection and mycotoxin concentrations in maize - E.D. Van Asselt; W. Azambuja; A. Moretti; P. Kastelein; T.C. De Rijk; I. Stratakou; H.J. Van Der Fels-Klerx (Food Additives & Contaminants: Part A, 2012)

Molecular characterization of two distinct strains of blueberry scorch virus (BlScV) in northern Italy - M. Moretti; M. Ciuffo; P. Gotta; D. Prodorutti; P. Bragagna; M. Turina (Archives of Virology, 2011)

Controlling a vancomycin-resistant enterococci outbreak in a Brazilian teaching hospital - M. L. Moretti; L. G. Oliveira Cardoso; C. E. Levy; A. Nowakosky; L. F. Bachur; O. Bratfich; M. L. Leichsenring; R. Fagnani; S. M. Peres Evangelista Dantas; M. R. Resende; P. Trabasso (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Scanning electron microscopy studies of cuticle micromorphology in Cycas L. (Cycadaceae) - J. E. Mickle; M. Rosaria Barone Lumaga; A. Moretti; P. De Luca (Plant Biosystems, 2011)

Spider, bee, and bird communities in cities are shaped by environmental control and high stochasticity - T. Sattler; D. Borcard; R. Arlettaz; F. Bontadina; P. Legendre; M. K. Obrist; M. Moretti (Ecology, 2010)
Spatially organized distribution patterns of species and communities are shaped by both autogenic processes (neutral mechanism theory) and exogenous processes (niche theory). In the latter, environmental variables that are themselves spatially organized induce spatial structure in the response variables. The relative importance of these processes has not yet been investigated in urban habitats. We compared the variance explained by purely spatial, spatially structured environmental, and purely environmental components for the community composition of spiders (Araneae), bees (Apidae), and birds (Aves) at 96 locations in three Swiss cities. Environmental variables (topography, climate, land cover, urban green management) were measured on four different radii around sampling points ( Our results suggest that the anthropogenic structuring of urban areas has disrupted the spatial organization of environmental variables and inhibited the development of biotic spatial processes. The near absence of spatial structure may therefore be a feature typical of urban species assemblages, resulting in urban community composition mainly influenced by local environmental variables. Urban environments represent a close‐knit mosaic of habitats that are regularly disturbed. Species communities in urban areas are far from equilibrium. Our analysis also suggests that urban communities need to be considered as being in constant change to adapt to disturbances and changes imposed by human activities.

Functional traits as indicators of biodiversity response to land use changes across ecosystems and organisms - Marie Vandewalle; Francesco de Bello; Matty P. Berg; Thomas Bolger; Sylvain Dolédec; Florence Dubs; Christian K. Feld; Richard Harrington; Paula A. Harrison; Sandra Lavorel; Pedro Martins da Silva; Marco Moretti; et al. (Biodiversity and Conservation, 2010)

Lipid-lowering drug use in Italian primary care: effects of reimbursement criteria revision - G. Trifirò; M. Alacqua; S. Corrao; S. Moretti; D. U. Tari; M. Galdo; A. P. Caputi; V. Arcoraci (European Journal of Clinical Pharmacology, 2008)

Within-field variability of Fusarium head blight pathogens and their associated mycotoxins - X.-M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2007)

Use and safety profile of antiepileptic drugs in Italy - M. L. Iorio; U. Moretti; S. Colcera; L. Magro; I. Meneghelli; D. Motola; A. L. Rivolta; F. Salvo; G. P. Velo (European Journal of Clinical Pharmacology, 2007)

Evaluation of Fusarium solani Hyphae and Conidia Susceptibility to Amphotericin B and Itraconazole: Study of a Clinical Case - A. B. A. Teixeira; M. L. Moretti; P. Trabasso; A. von Nowakonski; F. H. Aoki; A. C. Vigorito; M. Miyaji; K. Nishimura; H. Taguchi; A. Z. Schreiber (Mycopathologia, 2005)

Mainshocks and aftershocks of the 2002 molise seismic sequence, southern Italy - C. Chiarabba; P. De Gori; L. Chiaraluce; P. Bordoni; M. Cattaneo; M. De Martin; A. Frepoli; A. Michelini; A. Monachesi; M. Moretti; G. P. Augliera; E. D'Alema; et al. (Journal of Seismology, 2005)

Predominance and association of pathogenic fungi causing Fusarium ear blightin wheat in four European countries - X. -M. Xu; D. W. Parry; P. Nicholson; M. A. Thomsett; D. Simpson; S. G. Edwards; B. M. Cooke; F. M. Doohan; J. M. Brennan; A. Moretti; G. Tocco; G. Mule; et al. (European Journal of Plant Pathology, 2005)

Relationship between the incidences of ear and spikelet infection of Fusarium ear blight in wheat - X.-m. Xu; D.W. Parry; S.G. Edwards; B.M. Cooke; F.M. Doohan; A. Maanen; J.M. Brennan; S. Monaghan; A. Moretti; G. Tocco; G. Mule; L. Hornok; et al. (European Journal of Plant Pathology, 2004)

Molecular phylogenetics of Dipsacaceae reveals parallel trends in seed dispersal syndromes - P. Caputo; S. Cozzolino; A. Moretti (Plant Systematics and Evolution, 2004)

Phaeohyphomycosis Caused by Chaetomium Globosum in an Allogeneic Bone Marrow Transplant Recipient - A.B.A. Teixeira; P. Trabasso; M.L. Moretti-Branchini; F.H. Aoki; A.C. Vigorito; M. Miyaji; Y. Mikami; M. Takada; A.Z. Schreiber (Mycopathologia, 2003)

Liquefaction and fluidization structures in Messinian storm deposits (Bajo Segura Basin, Betic Cordillera, southern Spain) - P. Alfaro; J. Delgado; A. Estévez; J. Molina; M. Moretti; J. Soria (International Journal of Earth Sciences, 2002)

Molecular tagging of the Am gene from Lycopersicon hirsutum f. glabratum PI 134417 using AFLP markers - G. Parrella; I. Hochu; K. Gebre-Selassié; P. Gognalons; A. Moretti; G. Marchoux; C. Caranta (Acta Physiologiae Plantarum, 2000)

Nimesulide and renal impairment - R. Leone; A. Conforti; E. Ghiotto; U. Moretti; E. Valvo; G. P. Velo (European Journal of Clinical Pharmacology, 1999)

Morphological aspects of stomata, cuticle and chloroplasts in ceratozamia kuesteriana regel ( Zamiaceae) - M.R. Barone Lumaga; A. Moretti; P. De Luca (Plant Biosystems, 1999)